ROLE OF TRANSPORT IN REALISING THE SUSTAINABLE DEVELOPMENT GOALS (Perner's Contacts, 2019)
Transport is a vital enabler of several SDGs. It contributes strongly to the SDGs regarding economic development, industry and SMEs, as well as trade and investment. Consequently, it also helps achieve the SDGs that aim to promote employment and well-being, and to reduce inequalities and exclusion. Meanwhile, transport presents many challenges with respect to the SDGs, such as the need to reduce climate and environmental impacts, to improve transport systems and traffic safety, and to manage concerns related to jobs and decent work. The goal of this paperis to provide analysis of aspects of sustainable development in relation to transport in terms of fulfillment of selected goals of Agenda 2030. Presented contribution is part of solution of Project Vega č. 1/030218 „Smart cities as a possibility for implementation of the concept of sustainable urban development in the SlovakRepublic“.
Keywords: sustainable growth; goals the Agenda 2030; transport